PENANAMAN NILAI DALAM PENGUATAN PENDIDIKAN KARAKTER DI SMP NEGERI 8 YOGYAKARTA - Pratiwi, Eka (Fakultas Ilmu Pendidikan, 2021)
The purpose of this research is to describe the inculcating value in strengthening character education in SMP Negeri 8 Yogyakarta. This research is a descriptive qualitative research. The subjects in this research were the principal, educators, students and parents/ guardians of students. Data collection techniques were using observation, interviews, and documentation. The data analysis technique used the Milles and Huberman model, namely using the data condensation step, presenting the data, and drawing conclusions. Test the validity of the data in this research using triangulation. The research results showed that: (1) Guidelines in inculcating values with the 2013 curriculum, syllabus and document books (rules of conduct). (2) The process of inculcating character values at SMP Negeri 8 Yogyakarta uses three ways, namely by providing understanding / knowledge, through habits, and through good examples conducted by school principals and educators. (3) The values implanted are religious, nationalist, independent, mutual assistance and integrity values. (4) The supporting factors are the culture of the school, facilities and infrastructure, good relationship with the school community. The inhibiting factor is the understanding of different school members about character education, so it takes patience and hard work from the school in an effort to equalize perceptions so that the implementation of character education is as expected, educators who have not maximally provided understanding, and low parental understanding.Â Â Keywords: Inculcating Value, PPK